The Effect of Variations in Mixtures of Copper and Graphite Powder on Electrical Conductivity, Bending Strength, and Microstructure of Polymer Conductor Plates - Thaib, Hamdi; Panuh, Dedikarni (UIR PRESS, 2026)
Polymer conductor plates are made from a Polymer Matrix Composite (PMC) comprising non-metallic particles and a polymer matrix. One effective conductor of electric current is copper. This study was conducted to investigate how different mixtures of copper and graphite powder affect electrical conductivity, bending strength, and microstructure of the polymer conductor plate. The study tested various mixtures of copper powder, graphite, and epoxy resin in proportions of 15%: 75%: 10%, 20%: 70%: 10%, and 25%: 65%: 10%. The highest electrical conductivity and bending strength were observed in sample 3, which contained 25% copper powder, 65% graphite, and 10% epoxy resin. For comparison, a pure copper (100%) reference sample was also tested, yielding an electrical conductivity of 6.25 S/cm as a benchmark for the maximum achievable value. This is due to the greater amount of copper powder, which reduces resistance in the polymer conductor plate. Lower resistance in the polymer conductor plate allows easier current flow; thus, lower resistivity enhances its electrical conductivity. A high bending strength is achieved because copper is a malleable metal that can withstand directional loads. This is evident from the microstructure test results, where a higher copper content correlates with higher electrical conductivity and bending strength.